Hubungan Sarapan Pagi Dengan Prestasi Belajar Mahasiswa Tingkat 2 Prodi 03Keperawatan Stikes Bina Schat Ppni Mojokerto - Peni, Tri; Eko Setiawan, Danes (JURNAL KEPERAWATAN BINA SEHAT, 2017)
AbstractMeal or breakfast are still considered dull habits. No breakfast habits in light of the purpose of health and nutrition for childrens achievement is declining is a mistake that is very detrimental for the future of teenagers. The purpose of this study determine the relationship breakfast with student learning achievement level 2 Prodi 03 in Iursing high school of healt wellness PPNT Mojokerto . The design used in this study is an analytic correlation with cross sectional approach. a population of 140 students to 103 students obtained samples taken by simple random sampling. This study uses the independent variables and the dependent variable is a full breakfast with student achievement. Data retrieved by using questionnairs and KHS. Results showed students who regularly eat breakfast in the morning, 54respondentsor 52.42% as well as students with learning achievement is very satisfying that 79 respondents or 76.70%,and the majority of respondents were regular morning breakfast routine has a very satisfactory achievement learn that as many as 40 respondents or 50.63%. Spearman rho test results with the help of SPSS 20.0. show pvalue = 0.00 or <0.05 means that HI is accepted, so there is a relationship with a full breakfast with student learning achievement level 2 coaching academy healthy nursing PPNl Mojokcrto. The more routine breakfast to students, increasing both the achievement of students.Keyword: Breakfast, learning achievement